PERBANDINGAN KADAR HEMOGLOBIN DAN MCV SEBAGAI INDIKATOR ANEMIA DEFISIENSI BESI PADA IBU HAMIL TRIMESTER I DAN TRIMESTER III DI PUSKESMAS MAJENANG I - Damara Desiyanti; Yusuf Eko Nugroho; Meka Faizal Farabi (Klinikal Sains : Jurnal Analis Kesehatan, 2026)
Pregnancy is a condition in which the ovum and sperm meet. Changes during pregnancy include changes in erythrocyte mass, plasma volume, and blood volume, resulting in low hemoglobin (Hb) levels due to a decrease in erythrocyte in the blood. Anemia is a global health problem, especially in developing countries, with an estimated 30% of the world’s population suffering from anemia. Anemia is common in the community, especially among pregnant women. Anemia in pregnant women that is not treated properly can increase the risk of dangerous complications, such as premature labor. In addition, anemia can also increase the risk of low birth weight in babies. On the mother’s side, anemia can increase the risk of postpartum depression and postpartum maternal mortality. The purpose of this study was to determine the comparison of hemoglobin and MCV levels as indicators of iron deficiency anemia in pregnant women in the first and third trimesters at the Majenang I Community Health Center. This was an observational analytical study with a cross-sectional approach, with samples taken at the Majenang I Community Health Center from September 2024 to April 2025 according to the inclusion and exclusion cricetria, totalling 33 samples. The results showed a significant difference in hemoglobin levels between at first trimester (average 11.97 g/dL) and the third trimester (11.00 g/dL). Additionally, there was a significant difference in MCV values between the two groups. The average MCV value increased from 82.75 in the first trimester to 84.12 in the third trimester. The increase in MCV values was still within the normocytic range and reflected the adaptation of erythropoiesis during pregnancy. The conclusion of this study is that there are differences in hemoglobin and MCV levels in pregnant women in the first and third trimesters at the Majenang I Community Health Center. Both hemoglobin and MCV levels undergo significant changes and can be used as early indicators in detecting iron deficiency anemia in pregnant women.